Rapid nutrient evaluation of sorghum silages using two types of near-infrared reflectance spectroscopy - Budiongo, K.J.; Harbers, L.H.; Seabourn, B.W.; Bolsen, K.K.; Brent, B.E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
This research was designed to develop a set of prediction equations to measure nutrient composition of Kansas sorghum silages using both a portable and a research type near-infrared spectrometer (NIRS). A robust set of equations for dry matter, crude protein, neutral detergent fiber, and acid detergent fiber was developed for a wide range of sorghum phenotypes . NIRS analysis of sorghum silages is feasible with both a tilting filter (portable) and research instrument with a grating monochrometer.
Keywords: Beef; Sorghum silage; Nutrient content; Near-infrared reflectance spectroscopy